-m+9=5m-45

Simple and best practice solution for -m+9=5m-45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m+9=5m-45 equation:


m in (-oo:+oo)

9-m = 5*m-45 // - 5*m-45

9-m-(5*m)+45 = 0

9-m-5*m+45 = 0

54-6*m = 0 // - 54

-6*m = -54 // : -6

m = -54/(-6)

m = 9

m = 9

See similar equations:

| -k+10=k+26 | | -4x-24=4 | | 8+5x=-6x+52 | | k-8=52-5k | | 2k-2=5k+1 | | -7w+8=-56+w | | -4-3w=2w-14 | | 5x-1=4x+2 | | -10(2x-14)-6x=70 | | -6m+4=2m+84 | | -5+6d=-6d+127 | | -k-6=3k+22 | | -7b+8=-2b-17 | | -3a+4=4a+39 | | 5a+8=-2+4a | | -6m-8=6+m | | y=-2/5-3 | | 3d+2=5d-22 | | 6x+4=94-3x | | a+5=6a+50 | | -8-2d=6d-16 | | -4+5n=6n-6 | | 5a+10=a+2 | | 4-3d=-2d+13 | | 7x-6x-1=6 | | -2k-3=-6+k | | -7t+1=7t-139 | | 3+3x=4x+9 | | 7-7a=7a-161 | | 6+2n=4n+28 | | m-9=36+6m | | -5m-1=-57+3m |

Equations solver categories